A new genus and species of odiniids (Diptera: Odiniidae) from the canopy of the Brazilian Amazon rainforest - Limeira-De-Oliveira, Francisco; Marques, Dayse Willkenia A.; Gaimari, Stephen D.; Rafael, José A. (Zootaxa, 2020)
Umbodinia bella gen. nov. et sp. nov. is described and illustrated from specimens collected in the canopy of an ombrophilous Amazonian forest, Manaus, Brazil. The genus is characterized by a unique combination of diagnostic features: body predominantly yellow; frons with two shiny dark brown to black lobules in lower corners, between the lunule and eye margins; lunule high-arched with two subtriangular spots covered with black pubescence; parafacial with tufts of long and strong setae, almost as long and stout as the fronto-orbital setae; and anepisternum with setulae dorsally and posteriorly, in addition to posterior setae.